2018
DOI: 10.1210/en.2018-00235
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Corticotrope Gene Expression Upon Increased Expression of Peptidylglycine α-Amidating Monooxygenase

Abstract: Throughout evolution, secretion has played an essential role in the ability of organisms and single cells to survive in the face of a changing environment. Peptidylglycine α-amidating monooxygenase (PAM) is an integral membrane monooxygenase, first identified for its role in the biosynthesis of neuroendocrine peptides released by the regulated secretory pathway. PAM was subsequently identified in Chlamydomonas reinhardtii, a unicellular green alga, where it plays an essential role in constitutive secretion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…The generation of a PAM-derived COOH-terminal fragment called sfCD, which enters the nucleus (25), led to studies on the effects of PAM on gene expression. We know from our studies in a doxycycline-inducible corticotrope tumor cell line that a 2-d 100-fold increase in PAM expression (up close to the level in the adult atrium) altered the expression of a few hundred genes (10). The altered atrial gene expression observed here could reflect the absence of PAM itself or a compensatory response to the consequences of lacking PAM expression since conception.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The generation of a PAM-derived COOH-terminal fragment called sfCD, which enters the nucleus (25), led to studies on the effects of PAM on gene expression. We know from our studies in a doxycycline-inducible corticotrope tumor cell line that a 2-d 100-fold increase in PAM expression (up close to the level in the adult atrium) altered the expression of a few hundred genes (10). The altered atrial gene expression observed here could reflect the absence of PAM itself or a compensatory response to the consequences of lacking PAM expression since conception.…”
Section: Discussionmentioning
confidence: 58%
“…The x axis is log 2 of the ratio (WT/knockout [KO]); the y axis is −log10 of the DESeq2 P value (up is more significant). Transcripts with blue dots were decreased when PAM was induced in pituitary cells in our previous study (10), while red dots indicate transcripts increased when PAM was induced. Gray dots indicate transcripts expressed at low levels in pituitary cells (FPKM < 3).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations